The Limitations of Overtime Limits to Reduce Long Working Hours: Evidence from the 2018-2021 Working Time Reform in Korea - Stéphane Carcillo; Alexander Hijzen; Stefan Thewissen (Institute of Labor Economics (IZA), 2023)
This paper provides a first assessment of the causal impact of the 2018-2021 reform in Korea meant to combat its long working-hour culture. The reform consists of lowering the statutory limit on total weekly working hours from 68 to 52. We apply a difference-in-difference approach in which we take advantage of the stepwise implementation of the reform by firm size using individual-level data. We present three main findings. First, the introduction of the 52-hour limit reduced but far from eliminated the incidence of working more than 52 hours. Second, there is some evidence that the introduction led to a reallocation of working hours, with more employees shifting from working fulltime to working overtime within the new limit (41-52 hours). Third, and more tentatively, this reallocation more likely took place within firms to account for fewer overtime hours worked by their employees, rather than within households to compensate for any income effects. Overall, our results show that a lower statutory limit can help to lessen a long working-hour culture, but is an insufficient measure by itself to fully eradicate it.
Keywords: J16; J22; K31; 330; working time regulation; working hours; time use; labour legislation; overtime; reallocation